IMPLEMENTATION OF REMEDIAL TEACHING IN OVERCOMING STUDENTS' LEARNING DIFFICULTIES IN FIQIH SUBJECTS IN MADRASAH - Maula, Nikmatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Madrasah is one of Islamic education institutions that develops in Indonesia cultivated in addition to mosques and boarding schools. In the process of learning Islamic Education in madrasah, learning activities cannot always run smoothly. So students seem slow to do tasks related to learning activities. This learning difficulties are already a common problem that occurs in the learning process. The phenomenon of learning difficulties, especially the subjects of Fiqh experienced by students at Darul Lughah Wal Karomah Islamic Senior High School usually seems clear from the decline in academic achievement or learning achievement. To prevent and overcome the causes of student learning difficulties, one alternative that can be taken in overcoming learning difficulties is to conduct remedial teaching. The results of this study are as follows; (1) The causes of learning difficulties faced by students in Fiqh at Darul Lughah Wal Karomah Islamic Senior High School subjects include; The language of the teacher is poorly understood by students, poor psychology or mental atmosphere of the students, and the unrelevant motivation from the teachers to the students. (2) The implementation of remedial teaching in the learning of Fiqh at Darul Lughah Wal Karomah Islamic Senior High School Kraksaan Probolinggo is applied by giving re-learning with different methods and media, giving special guidance, increasing training tasks, and giving intensive training.